Parental Misperceptions of Children's Underweight Status: A Meta-analysis. Issue 2 (14th January 2014) - Lundahl, Alyssa; Kidwell, Katherine M.; Nelson, Timothy D.
Abstract: Background: Accurate parental perceptions of their children's underweight status are needed to prevent overlooking potential disordered eating patterns or health conditions affecting growth. Purpose: The aim of this study is to determine overall proportion of parents who misperceive children's underweight status and correlates of such misperceptions. Methods: Original studies published to January 2013 were chosen through a literature search in established databases. Studies included assessed parental perceptions of their children's underweight and then compared perceptions to recognized standards for defining underweight based on anthropometric measures. Random- and mixed-effects models were used. Results: Thirty-seven articles (representing 39 studies; N = 4, 039) were included. Pooled effect sizes indicated that 46.58 % (95 % CI 40.90–52.35 %) of parents misperceive their children's underweight status, though the extent of misperceptions depended on a number of moderators. Conclusions: Nearly half of parents perceive their underweight children as weighing more than they actually do. Health care professionals are well positioned to take steps to remedy misperceptions and encourage healthy behaviors.